Preparing the Greek Revolution in Odessa in the 1820s: Tastes, Markets and Political Liberalism - Sifneos, Evrydiki (The Historical Review/La Revue Historique, 2014)
The article highlights the port-city space of Odessa during the first three decades of its foundation as an important hub of commercial activity, maritime trade and political liberalism in southern Russia. It emphasizes the role of multiple markets based on imported and local trade goods and describes the different ethnicities involved in foreign trade, focusing on merchants of Greek origin, their participation in the Philiki Etaireia and their degree of involvement in its organizational mechanisms. I attempt to read the Philiki Etaireia’s development and its influence on the Eastern Question and Russian-Ottoman relations in light of the general political fermentation that was taking part in the Russian Empire, mainly through the creation of secret societies within the Russian army. I believe that the Russian authorities, being involved in the general mobility and movement of ideas, influenced by the Western experiences of the Russian military, had to deal primarily with major political issues that left aside, at least at a regional level, movements of the same character that concerned the Greeks. In this positive political climate the “commercial outlook” of the Greek revolutionaries gave them the necessary coverage to act and move relatively freely.